Entrepreneurship Skills needed by Youths for Employment in Regulated Starch Production Occupations in Abia State - A.U., Onuka (Journal of Home Economics Research, 2024)
The Study focused on entrepreneurship skills needed by youths for employment in regulated starch production occupations in Abia state. The study adopted survey research design. Three research questions were answered and three hypotheses tested. The population was 127, made up of 45 registered women in starch production occupations and 82 extension agents. Questionnaire was used for data collection. Data were analyzed using mean, standard deviation and t-test. Findings include needed entrepreneurship skills in planning, production and marketing of starch to succeed in regulated starch production occupations. There was no significance difference in the mean ratings of the responses of the women and extension agents. It was recommended, among others, that, Abia State government will integrate the findings of the study into her Skill Acquisitions Centres.